Catechol-Containing acrylic poly(ionic liquid) hydrogels as bioinspired Filters for Water decontamination - Gallastegui, Antonela (2019)
Mussel inspired catechol containing materials have currently drawn great attention as biomaterials, adhesives, surface coatings and in bioelectronics, among other applications. In this work, we mimicked the ability of mussels as water filtration systems to adsorb organic and inorganic contaminants. For this purpose, the synthesis of biomimetic hydrogels by co-polymerization of a new ionic monomer, dopamine methacrylic acid salt (iDA) with a series of water soluble methacrylate monomers was performed using visible light photopolymerization. The iDA ionic monomer is highly water soluble as compared to previous reported monomers containing catechol groups. This allows its incorporation into different acrylic hydrogels in concentrations up to 50 % mol of monomers containing catechol groups, leading to functional materials with variable morphology and swelling properties. The hydrogels displayed to be highly effective for the removal of heavy metals such as As(V) and Cr(VI) with very good effectiveness compared to other commonly employed natural sorbents, such as clays. Additionally, these poly(ionic liquid) hydrogels containing catechol groups were evaluated in the removal also of other pollutants such as charged organic dyes. Preliminarily results demonstrate the versatility of these materials that combine catechol and ionic chemistry for the adsorption of a wide variety of water pollutants.